2009
DOI: 10.3810/pgm.2009.03.1991
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Hyponatremia in Hospitalized Patients: A Retrospective Cohort Study

Abstract: Hyponatremia at admission was associated with increased LOS and cost of care for hospitalized patients. Interventions or pharmacotherapies for the prompt treatment of hyponatremia could potentially reduce morbidity and LOS, thereby reducing the utilization of health care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 30 publications
5
62
1
2
Order By: Relevance
“…The results of this study are consistent with others in showing that HN patients use healthcare services more extensively, and represent a patient population which is more expensive to treat in the inpatient setting. 5,22 Additionally, this study yields new findings in that patients in the real-world with hyponatremia resulting from various etiologies are more likely to be readmitted to the hospital than patients with similar demographics and characteristics who do not have hyponatremia. The results of the subgroup analysis were generally consistent with the results for the overall matched population, as the incremental burden estimates were directionally consistent.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The results of this study are consistent with others in showing that HN patients use healthcare services more extensively, and represent a patient population which is more expensive to treat in the inpatient setting. 5,22 Additionally, this study yields new findings in that patients in the real-world with hyponatremia resulting from various etiologies are more likely to be readmitted to the hospital than patients with similar demographics and characteristics who do not have hyponatremia. The results of the subgroup analysis were generally consistent with the results for the overall matched population, as the incremental burden estimates were directionally consistent.…”
Section: Discussionmentioning
confidence: 79%
“…Zilberberg et al and Callahan et al additionally reported that HN patients had a significantly greater need for ICU (4%-10%). 5,22 In the present study, LOS in the ICU and associated costs were also compared among HN and non-HN cohorts and, after adjustment for key patient characteristics, hyponatremia was associated with an incremental increase of 10.2% for ICU LOS and an 8.9% increase in ICU cost.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Callahan et al, [8], found that admissions with hyponatremia had significantly longer hospital length of stay than those admitted without hyponatremia. In our study the effect of hyponatremia on differences in mean time to improve has been ruled out as the serum sodium was comparable in both the groups.…”
Section: References Discussionmentioning
confidence: 99%
“…These adverse outcomes were more frequent even when serum [Na + ] was in the range of 130-134 mmol/L. 3,5,16 Furthermore, worsening of hyponatremia during hospitalization is associated with increased adjusted odds of in-hospital mortality 17 and discharge to short-or long-term care facilities. 5 …”
Section: Prognostic Implicationsmentioning
confidence: 99%